High expression of tissue O-linked glycans is associated with a malignant phenotype of cholangiocarcinoma. Issue 2 (February 2021) - Talabnin, Krajang; Talabnin, Chutima; Khiaowichit, Juthamas; Sutatum, Nuchanard; Asavaritikrai, Pundit; Suksaweang, Sanong; Tongtawee, Taweesak; Ishihara, Mayumi; Azadi, Parastoo; Sripa, Banchob
Objective: This study aimed to investigate the expression of O -linked glycoprotein glycans in tissue of patients with cholangiocarcinoma compared with adjacent normal tissue. Methods: Sixty patients with cholangiocarcinoma were included in the study. Permethylated O -linked glycans from intrahepatic cholangiocarcinoma tissue and adjacent normal tissue were analyzed using nano-spray ionization-linear ion trap mass spectrometry. Histochemistry of peanut agglutinin lectin was used for detection and localization of galactose (Gal) 1, N-acetyl-galactosamine (GalNAc) 1. Results: O -linked glycans from patients with cholangiocarcinoma were composed of di- to hexa-saccharides with a terminal galactose and sialic acids (N-acetylneuraminic acid [NeuAc]). A total of eight O -linked glycan structures were detected. Gal1GalNAc1 and Gal2 N-acetyl-glucosamine 1 GalNAc1 expression was significantly higher in tissue from patients with cholangiocarcinoma compared with adjacent normal tissue, while NeuAc1Gal1GalNAc1 expression was significantly lower. High Gal1GalNAc1 expression was significantly associated with the late stage of cholangiocarcinoma (stages II–IV), lymphatic invasion, and vascular invasion. Conclusion: Our study shows expression of O -linked glycans in progression of cholangiocarcinoma and highlights the association of Gal1GalNAc1 with lymphatic and vascular invasion of cholangiocarcinoma.